Investigation of the stability of Novozym® 435 in the production of biodiesel - José, Carla; Austic, Gregory B.; Bonetto, Rita Dominga; Burton, Rachel M.; Briand, Laura Estefania (Catalysis Today)
The effect of the composition of the feedstock (free fatty acids and methanol), the presence or absence of moisture and the contact with biodiesel on the catalytic, enzymatic and physical stability of Novozym® 435 during enzymatic biodiesel production was studied. The continuous removal of moisture leads to the deactivation of the biocatalyst and favours the degradation of the polymethylmethacrylate (PMMA) that constitutes the support of the Candida antarctica B lipase (CALB). Nevertheless, the presence of PMMA along with the active protein was detected in the reaction media regardless of the operating conditions. Surprisingly, biodiesel (without the presence of methanol) is able to diffuse inside the biocatalyst beads producing its swelling, modifying the internal texture and also dissolving the polymeric matrix. Fil: José, Carla. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas "Dr. Jorge J. Ronco". Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Ciencias Aplicadas; Argentina Fil: Austic, Gregory B. Piedmont Biofuels; Estados Unidos Fil: Bonetto, Rita Dominga. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas "Dr. Jorge J. Ronco". Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Ciencias Aplicadas; Argentina Fil: Burton, Rachel M. Piedmont Biofuels; Estados Unidos Fil: Briand, Laura Estefania. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas "Dr. Jorge J. Ronco". Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Ciencias Aplicadas; Argentina